The things of the Internet of Musical Things: defining the difficulties to standardize the behavior of these devices - Vieira, Rômulo; Gonçalves, Luan; Schiavoni, Flávio (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais do X Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2020)
Musical practice has always been susceptible to technological changes, adapting to the novelties that each era provided, such as, for example, the replacement of mechanical devices by electric ones or even the adhesion of magnetic tapes in the recording process. Nowadays, these technological transformations continue to influence music, especially when using concepts from the Internet of Things (IoT), creating a field called Internet of Musical Things (IoMusT). Although IoMusT helps with remote rehearsals, streamlines the recording process and allows the creation of participatory concerts, there is still no clear definition of how an object connected to this network should behave. In this context, this paper proposes software, hardware and communication protocols standards that these devices must follow, in order to improve the user experience and make this field more widespread and easier to understand. Issues that prevent this standardization are also discussed.